Factors associated with uptake of isoniazid preventive therapy among children living with HIV in Mwanza region, Tanzania: a cross-sectional study - Ally Tuwa; David Okia; Ritah Nantale; Hyasinta Jaka; Jimmy Patrick Alunyo; David Mukunya; Joseph KB Matovu; Dan Kibuule (BMC, 2024)
Abstract Background Tuberculosis (TB) is a leading cause of death among children living with HIV (CLHIV). Isoniazid preventive therapy (IPT) reduces the incidence of TB by 70% and mortality by 50% among CLHIV. However, in most developing countries including Tanzania, the uptake of IPT is suboptimal, below the 90% WHO-global uptake target. We assessed the factors associated with IPT uptake among CLHIV in Mwanza region, Tanzania. Methods This was a multicenter facility-based cross-sectional study among CLHIV aged 1 to 10 years in seven districts of Mwanza region, Tanzania from 1st November 2021 to 20th January 2022. Data were collected using a structured interview-administered questionnaire including information on children and caregivers' demographics, caregivers' health related information and children's clinical information. Our outcome variable was uptake of IPT, defined as initiation on IPT either during the time of the study or within past three years before this study We conducted modified Poisson regression to assess the association between IPT uptake and selected exposures in Stata version 15.0. Results A total of 415 CLHIV were enrolled, the median age of the children was 7 years (Interquartile range: 5-8). The uptake of IPT was 91% (n = 377). The majority of children's caregivers were HIV positive (86%, n = 387) and were aware about IPT (63.6%, n = 264). Factors associated with IPT uptake included; having an employed caregiver [Adjusted Prevalence Ratio (aPR): 1.06 95% Confidence Interval (CI): 1.00-1.13] and attending the ART clinic every month [aPR: 1.00; 95% CI: 0.87-1.00] . Conclusions The uptake of IPT uptake among CLHIV in Mwanza, Tanzania exceeds the global WHO-target of ≥ 90%. Monthly ART clinic visits could be essential in promoting IPT uptake among CLHIV.